Structure–activity relationship, in vitro and in vivo evaluation of novel dienyl sulphonyl fluorides as selective BuChE inhibitors for the treatment of Alzheimer's disease. (1st January 2021) - Wu, Chengyao; Zhang, Guijuan; Zhang, Zai-Wei; Jiang, Xia; Zhang, Ziwen; Li, Huanhuan; Qin, Hua-Li; Tang, Wenjian
Abstract: To discover novel scaffolds as leads against dementia, a series of δ-aryl-1, 3-dienesulfonyl fluorides with α-halo, α-aryl and α-alkynyl were assayed for ChE inhibitory activity, in which compound A10 was identified as a selective BuChE inhibitor (IC50 = 0.021 μM for eqBChE, 3.62 μM for hBuChE). SAR of BuChE inhibition showed: (i) o - > m - > p -; –OCH3 > –CH3 > –Cl (–Br) for δ -aryl; (ii) α-Br > α-Cl, α-I. Compound A10 exhibited neuroprotective, BBB penetration, mixed competitive inhibitory effect on BuChE ( K i = 29 nM), and benign neural and hepatic safety. Treatment with A10 could almost entirely recover the A β 1-42 -induced cognitive dysfunction to the normal level, and the assessment of total amount of A β 1-42 confirmed its anti-amyloidogenic profile. Therefore, the potential BuChE inhibitor A10 is a promising effective lead for the treatment of AD.